ART DESIGN AND CREATIVE CONCEPTS IN FASHION DESIGN - Yuryevna Ermilova, Daria; Borisovna Lyakhova, Nadezhda; Alexandrovich Popov, Stepan (Revista Inclusiones, 2020)
The study is devoted to the creative concept of art design in fashion design. The subject of research is design concepts in fashion design. The research topic is the diverse links between art and the fashion industry, which can be considered as the basis for the formation of the concept of art design. The purpose of the study is to identify the features of the interaction of art with the creative practice of fashion design and the reasons for representing the utilitarian object as a work of art. The hypothesis of the study is that the connection between art and the fashion industry can become an effective marketing strategy. The presentation of a design object as a work of art gives it additional symbolic value and increases the social status of its creator. The study applies a culturological approach, which considers project activities in connection with the realities of the era, and a systematic approach that allows identifying the connection of aesthetic theories with the practice of design, art history and stylistic analysis.